IMPLEMENTATION OF GRADE POINT AVERAGE SYSTEM AT A CLINICAL DEPARTMENT OF MEDICAL UNIVERSITY - Marina A. Ufimtseva; Yuriy M. Bochkarev; Irina F. Vishnevskaya (Высшее образование в России)
The system of training medical specialists in internship and residency is a priority direction in medical university. The specialized training program in the field of dermatovenereology, developed at the Department of Skin and Venereal Diseases of Ural State Medical Academy, involves using the grade point average system, which meets the current requirements and has proven its effectiveness in the learning process.